School principal as a change facilitator in ICT integration - Afshari, Mojgan; Kamariah, Abu Bakar; Wong Su Luan; Bahaman; Abu Samah; Foo Say Fooi (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.